2020
DOI: 10.3389/fphys.2020.568800
|View full text |Cite
|
Sign up to set email alerts
|

Newly Discovered Adipokines: Pathophysiological Link Between Obesity and Cardiometabolic Disorders

Abstract: With the increasing prevalence of obesity, obesity-related problems such as cardiometabolic disorders (CMD), are also rapidly increasing. To prevent and alleviate the progressive course of CMD, it is important to discover the pathophysiological mechanisms between obesity and CMD. Adipose tissue is now recognized as an active endocrine organ that releases adipokines. Adipokines play a pivotal role in chronic low-grade inflammation, oxidative stress, and impaired insulin signaling, contributing to metabolic dera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 66 publications
1
22
0
1
Order By: Relevance
“… 4 Adipose tissue is metabolically active and produces proinflammatory molecules, such as adipokines, which contribute to the chronic, low-grade inflammation found in patients with obesity. 6 Studies demonstrated that patients with obesity have higher levels of C reactive protein (CRP) and increased levels of proinflammatory cytokines, leading to additional recruitment of macrophages and further continuation of this proinflammatory process. 7 Diabetes, in addition to obesity, is also characterised by a proinflammatory state.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Adipose tissue is metabolically active and produces proinflammatory molecules, such as adipokines, which contribute to the chronic, low-grade inflammation found in patients with obesity. 6 Studies demonstrated that patients with obesity have higher levels of C reactive protein (CRP) and increased levels of proinflammatory cytokines, leading to additional recruitment of macrophages and further continuation of this proinflammatory process. 7 Diabetes, in addition to obesity, is also characterised by a proinflammatory state.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is an established risk factor for atherosclerosis and coronary artery disease (CAD) and can accelerate both conditions via a wide variety of actions, such as a rise in blood pressure and glucose concentration, abnormal lipid profiles, and most significantly, by creating a systemic inflammatory milieu. More importantly, a growing body of evidence suggests that many adipokines may directly mediate atherogenesis by affecting the function of endothelial cells, arterial smooth muscle cells, and macrophages within arterial walls [ 2 , 3 ]. The accumulation of visceral abdominal tissue (VAT) seems to be a hallmark feature of abdominal obesity and substantially contributes to metabolic abnormalities [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is an orexigenic hormone induced by fasting and produced by WAT, and increases food consumption and body weight through Agouti-related protein neurons (AgRP), and accelerates the production of liver glucose, activating the G protein-cAMP-protein kinase A (PKA) pathway [ 16 , 17 ]. In a clinical study, it was found that obese people have a high concentration of asprosin, and it is also closely related to insulin resistance in humans, which is proven when higher serum levels of asprosin are identified in patients with DM2 [ 49 ]. Asprosin levels are elevated in comorbidities such as obesity and DM2.…”
Section: Discussionmentioning
confidence: 99%